(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the amount of hours spent with TV/electronic games, anthropometric profile, cardiorespiratory fitness and socio-behavioral factors in schoolchildren. The sample consisted of 28 students, 14 boys and 14 girls, from the 6th year of the first segment of elementary education in the private school system in urban areas. A Socio-Behavioral Assessment Questionnaire was applied. Anthropometric measurements (height, total body mass and BMI) and the cardiorespiratory fitness test (running/walking - PROESP/Br). Regarding the existence of a leisure area (playground), 75% of the boys’ homes and 60% of the girls’ homes have a leisure area. Both groups indicated that they play with other children outside the school environment, 81.3% of boys and 66.6% of girls. As for activities outside of school, 68.7% of boys and 66.6% of girls prefer electronic games when they are not in school hours. Girls had significantly longer time using electronic devices compared to boys (Girls 466.0 ± 8.623 min; Boys 259.3 ± 12.71 min; p<0.0001). Only 35.7% of boys and 42.9% of girls were considered eutrophic. We conclude that the observed sample spend many hours of the day with TV/electronic games far above what is recommended by the World Health Organization (WHO). Most of the sample presented an inappropriate anthropometric and cardiorespiratory profile for the age group, and even with access to leisure areas, company for games and enjoying physical education classes, they prefer activities with TV/electronic games outside the school environment, showing a preference for sedentary leisure activities.